The political and demographic predictors of candidate emergence in city council elections - Krebs, Timothy B. (1999)
Legislative scholars have shown that candidates emerge when political conditions are most favorable. The topic of candidate emergence in city council elections is addressed using data collected on all 50 of Chicago's wards from 1979 to 1995. The results show that wards with open seats or vulnerable incumbents on the ballot generally have a larger and more politically experienced crop of candidates than other wards. The findings also reveal that wards with higher concentrations of black residents have significantly larger and more politically experienced candidate pools than wards with fewer blacks. Explanations for these findings are discussed. - Reproduced
Keywords: Local elections - United States; Elections - United States; Local government - United States; Local government